Patterns of Dengue Fever Incidence in West Kalimantan Province, Indonesia: Evidence from 2018–2022 Surveillance Data - Wa Ode Nur Safia; Syafiqah Rizky Ariesta Kamaluddin; Zalsabila Nur; Suci Ramadani; Wa Ode Suci Munawar (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a mosquito-borne infectious disease caused by the dengue virus and transmitted primarily by Aedes mosquitoes. Over recent decades, the incidence of DHF has increased substantially at both global and national levels, including in West Kalimantan Province, Indonesia. This escalating trend underscores the need for evidence-based and integrated vector control strategies to reduce disease morbidity and mortality. Objective: This study aims to describe the distribution and temporal trends of DHF cases in West Kalimantan Province from 2018 to 2022, with particular emphasis on incidence dynamics, environmental risk factors, and the role of vector control efforts. Methods: A quantitative descriptive study was conducted using secondary data obtained from the West Kalimantan Provincial Health Profile. Annual DHF case data were systematically analyzed and presented in graphical form, followed by narrative interpretation to identify distribution patterns and temporal trends over the study period. Results: The analysis revealed a fluctuating trend in DHF incidence between 2018 and 2022. A marked decline in reported cases was observed during 2020–2021, which is likely associated with reduced population mobility and public health restrictions during the COVID-19 pandemic. However, a resurgence of cases occurred in 2022. These fluctuations highlight the importance of sustained dengue control interventions, particularly in densely populated areas and environments conducive to mosquito breeding. Community knowledge and preventive behaviors, including the implementation of mosquito nest eradication (PSN), were found to play a crucial role in influencing DHF incidence. Additionally, environmental conditions, sanitation, and population mobility emerged as key determinants of dengue transmission. Conclusion: DHF incidence in West Kalimantan exhibited significant temporal variation from 2018 to 2022. Strengthening community education, promoting 3M practices, and implementing sustainable vector control innovations are essential to effectively reduce dengue transmission.